Religiusitas dalam Novel Surat Cinta dari Bidadari Surga Karya Aguk Irawan - Gustiana, Lina; Praptanti, Isnaeni; Pamungkas, Onok Yayang (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Research on religiosity has received important attention by academics. However, there are still few researchers who actually discuss religiosity in literature. Religiosity is religious knowledge, feelings, and actions that arise in oneself. This research identifies religiosity in Aguk Irawan's novel Love Letter from the Angel of Heaven (hereinafter referred to as SCDBS). The method used in this study is descriptive quantitative, with the research subject coming from the novel SCBD. The subject of the study comes from Aguk Irawan's 312-page SCBDS novel literary work . The research data is descriptive data in the form of texts, sentences, and expressions in SCDBS novels that contain elements of religiosity. The source of the research data is SCDBS. The data collection technique used in this study is a literature study technique. Data analysis techniques are carried out by means of 1) reading novels; 2) categorize the data according to the research focus; 3) analyze the data; 4) make a temporary conclusion; 5) data verification; 6) make a final conclusion. The results showed that the eligiusity contained in this novel is the dimension of belief, the dimension of religious practice, the dimension of passion, the dimension of religious knowledge and the dimension of experience and consequences. The dimension of belief found in this novel is in the form of faith in Allah totaling eight data, faith in the Messenger of Allah one data, dimension of religious practice, namely prayer as many as three data, dimension of passion in the form of gratitude, and prayer each amounting to one data, and miracles, dimension of religious knowledge, namely learning religion a number of one data, and the dimension of consequences found is the act of not drinking a number of one data. Research implications that the representation of religiosity is not only in the practice of life, but also in narrative works. Keywords: Religiosity, Novel, Surat Cinta dari Bidadari Surga, Aguk Irawan